Adolescent pregnancy: maternal and fetal outcomes in patients with and without preeclampsia - Bakwa-Kanyinga, Felly; Capp, Edison (Pregnancy Hypertension, 2017)
Objective: To determine the prevalence of preeclampsia (PE) in adolescents and to evaluate its association with risk factors for, and the occurrence of, adverse maternal and fetal outcomes. Results: Of 3006 deliveries, 533 (17.7%) were from teenage mothers, with twenty-eight (5.3%) presenting PE; 17.8% of these cases were classed as severe. Vitamin and mineral supplementation was associated with the occurrence of PE (p=0.034). Puerperal complications and prematurity were more frequent in the PE group. Conclusions: Prevalence of PE among adolescents was similar to the literature data and was associated with high rates of preterm birth and puerperal complications.